Poverty, Inequality, and Agriculture in the EU - Azevedo, Joao Pedro (World Bank, Washington, DC, 2018)
Boosting convergence and shared prosperity in the European Union achieved renewed urgency after the global financial crisis of 2008. This paper assesses the role of agriculture and the Common Agricultural Program in achieving this. The paper sheds light on the relationship between poverty and agriculture as part of the process of structural transformation. It positions each member country on the path toward a successful structural transformation. The paper then evaluates at the regional level where the Common Agricultural Program funding tends to go, poverty-wise, within each country. This approach enables making more informed policy recommendations on the current state of the Common Agricultural Program funding, as well as evaluating the role of agriculture as a driver of shared prosperity. The analysis performed throughout the paper uses a combination of data sources at several spatial levels.